Introducing Vol. 12 No. 1 - Kim, Min Seong (Sanata Dharma University, 2024)
The first article in this issue of Retorik, “Human’s and Nonhuman’s Negotiations after the Conversion of the Function of Mangrove Forests into Salt Mines” by Eventus Ombri Kaho, examines the transformation in the relationship between humans and nonhumans following the conversion of mangrove forests to salt mines in East Nusa Tenggara. From a posthumanist perspective that draws from Donna Haraway and Rosi Braidotti, Kaho examines how the intimate relation between the inhabitants of the Weseben village with the mangrove forest were lost due to the salt mine development and goes on to consider how the damaged human-nonhuman “kinship” might be recovered.